Size Distribution of Black Gonggong Snail Canarium urceus, Linnaeus 1758 Based on Seagrass Percent Cover in Malalanda Village, Kulisusu District, North Buton Regency - Ishak, Ermayanti; Lilian, Lilian; Oetama, Dedy; Erawan, Muhammad Trial Fiar (Jurnal Biologi Tropis, 2024)
The aquatic of Malalanda village have a seagrass beds which are a living habitat for the Canarium urceus gastropod species. These snails are used by local people as a source of food. The aim of this research was to determine the size distribution of C. urceus based on different seagrass density in the seagrass ecosystem. The sampling duration was one month (from February to March 2023) in Malalanda, Kulisusu District, North Buton Regency, Southeast Sulawesi. The distribution of location sampling points used a purposive sampling method based on seagrass density. Sampling of C. urceus is a systematic random sampling method which was collected manually used hand. Station I with a seagrass density condition was 81,09% (very dense category) found a size distribution ranged from 31.5 to 38.6 mm, station II with a seagrass density condition was 38,73% (medium category) found a size distribution ranged from 27.9-31.4 mm, and station III with a seagrass density was 52,45% (dense category) found a size distribution ranged from 35.1-38.6 mm.